2019
DOI: 10.1186/s40494-019-0262-1
|View full text |Cite
|
Sign up to set email alerts
|

Azurite in medieval illuminated manuscripts: a reflection-FTIR study concerning the characterization of binding media

Abstract: In illuminated manuscripts, a reliable identification of oxyanion pigments such as azurite by rFTIR is simple, as several combination and overtone bands are strongly enhanced compared to transmission mode. However, the characterization of the used binding media is rather difficult, as the analysis of four medieval manuscripts from the late thirteenth to the fifteenth century (e.g. Cod. slav. 8 in the collection of the Austrian National Library), as well as the earliest known map of Vienna (Albertinischer Plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Calcium soaps were also identified on the surface of medieval illuminated parchment manuscripts (Vetter, Latini, and Schreiner 2019), likewise correlated with the presence of an organic binder. The presence of zinc soaps could therefore be correlated with the presence of fatty acids (as a result of the interaction of the fatty acid fractions with a zinc compound) originating from an oil-or an egg-based binder that was used to treat the surface of the manuscript.…”
Section: Fourier Transform Infrared Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…Calcium soaps were also identified on the surface of medieval illuminated parchment manuscripts (Vetter, Latini, and Schreiner 2019), likewise correlated with the presence of an organic binder. The presence of zinc soaps could therefore be correlated with the presence of fatty acids (as a result of the interaction of the fatty acid fractions with a zinc compound) originating from an oil-or an egg-based binder that was used to treat the surface of the manuscript.…”
Section: Fourier Transform Infrared Analysismentioning
confidence: 84%
“…The presence of zinc soaps could therefore be correlated with the presence of fatty acids (as a result of the interaction of the fatty acid fractions with a zinc compound) originating from an oil-or an egg-based binder that was used to treat the surface of the manuscript. The presence of a lipid component would also explain the strong C-H absorptions observed at 2,920 cm −1 and 2,850 cm −1 , moreover as these absorptions appear strongly correlated with the absorptions of the zinc carboxylates (Vetter, Latini, and Schreiner 2019). A small fraction lipid, typically between 0.2 and 3.0% (Možir et al, 2014), could also be due to amino acid residues of the polypeptide chains found in leather, but these are typically characterized by weak C-H stretching modes (Manfredi et al, 2015).…”
Section: Fourier Transform Infrared Analysismentioning
confidence: 90%
“…The identification of azurite (Cu 3 (CO 3 ) 2 (OH) 2 ) in the Vienna Moamin has already been published in an rFTIR study discussing the characteristic spectral features of the pigment mixed with various binding media [ 30 ]. XRF detection of Cu supported the rFTIR results.…”
Section: Resultsmentioning
confidence: 99%
“…The bands in the fingerprint region of the absorption index spectra match with the IRUG references azurite MP00001 and lead white MP00107 (see Additional file 7 ). Furthermore, two characteristic bands at 4378 cm −1 (overtone 3ν 3 ) and 4244 cm −1 (combination ν + δ O–H) in the rFTIR spectrum enable an easy identification of azurite [ 30 ]. The ν 3 asymmetric stretching vibration of azurite at around 1400 cm −1 overlaps with the analogous feature of lead white.…”
Section: Resultsmentioning
confidence: 99%
“…Artesani et al [4] proposed a combined-microscopy approach based on time-resolved photoluminescence (TRPL) micro-imaging and micro-Raman spectroscopy for studying a corpus of stratigraphic micro-samples from Russian Avantgarde modern paintings which allowed them to identify several inorganic pigments. Identification of azurite pigment and the binding media by reflection-FTIR method was the aim of the study carried out by Vetter et al [5] on medieval illuminated manuscripts belonging to Austrian National Library and Wien Museum. Albrecht et al [6] used the quantitative elemental analysis of the ground layer composition of 39 paintings and PCA analysis for an in-depth technical and art historical research of Jan Steen's oeuvre.…”
mentioning
confidence: 99%